INTEGRASI KEBIJAKAN DIVERSI BERBASIS PRINSIP KEADILAN RESTORATIF DALAM SISTEM HUKUM CUKAI DI INDONESIA - Muhardi , Dedi; Fahmi, Fahmi; Libra, Robert (JOURNAL EQUITABLE, 2025)
This research discusses the implementation of diversion policies based on restorative justice principles in Indonesia's customs sector, aimed at reducing the burden on the judicial system and restoring the country's economic losses. The research questions in this study focus on how diversion policies can be integrated into the customs legal system in Indonesia and the benefits and challenges faced to improve the effectiveness of law enforcement and economic recovery. The study uses normative legal research methods with library research, analyzing relevant regulations, doctrines, and legal theories. The findings indicate that the implementation of diversion policies can reduce judicial burdens, speed up economic recovery, and create a more efficient and just legal system. However, the main challenges include lack of understanding among law enforcement, unclear implementation regulations, and legal uncertainties. Policy reforms and increased capacity of law enforcement are crucial to ensure the successful implementation of this policy.